ADVANCE DIRECTIVES IN NURSING HOMES: BETWEEN AUTONOMY AND DISPOSSESSION - BOURDAIRE-MIGNOT, Camille; GRUNDLER, Tatiana (MEDECINE LEGALE DROIT MEDICAL, 2025)
People living in nursing homes are at the end of their lives and are at risk of su ering from cognitive illnesses. For these reasonsce in these establishments: theytend to generalize advance directives upon resident entry. However, we must remain vigil they could appear to be the privileged users of advance directives. In recent years, we have also observed a new practiant because the directives are poorly known and poorly used in nursing homes. However, they could prove to be quite useful, but only if they are rethought.